THE BASICS OF DEVELOPING TECHNIQUES AND TACTICS OF MOVING WITH THE BALL IN A FOOTBALL GAME - Muminov Feruz Ilxomovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article, the basics of the technique and tactics of ball throwing in a football game are important for practitioners and should be widely applied in practice, as well as the social and biological aspects of the process of training athletes the principles of interaction between the rate of swelling are discussed.